KEPASTIAN HUKUM MEKANISME PENINJAUAN KEMBALI KEDUA DALAM HUKUM ACARA PERDATA DI INDONESIA : Legal Certainty of the Second Review Mechanism in Civil Procedure Law in Indonesia - Wildan Arif Husen; Rinandu Kusumajaya Ningrum (Reformasi Hukum Trisakti, 2026)
Legal certainty is a key pillar in the civil law judicial system in Indonesia. Civil procedure law regulates the existence of stages of legal remedies, both ordinary and extraordinary, with its provisions. Normatively, a judicial review (PK) can only be filed once against a final and binding decision. In practice, Second Review is a response to conflicting decisions or new evidence that was not resolved in the First Review. The research question in this study is how the Second Review Mechanism in Indonesia works and what legal certainty the parties involved have. This research uses a normative juridical method, and the analysis is conducted qualitatively. Based on the discussion and conclusions, mechanism for a Second Review has not been explicitly regulated in legislation, but in practice, it can be applied by the judiciary under certain circumstances. The Second Review still be applied in a limited manner, particularly if there is a conflict of decisions or if decisive new evidence is found. The Second Review balances legal certainty with substantive justice, while at the same time affirming the need for clear normative regulations to avoid legal uncertainty.